(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The article focuses attention on the questions that AI and robotics, as an embodiment of AI, pose to Christian theology, with particular reference to origin, creation, and the limit. According to Christian theology, it is not conceivable that the act of producing AI machines and its result are comparable with the creative act for which the human exists, with a dignity that is ultimately based on its transcendence and destination to the communion with God. Christian theology considers it useful and necessary that we discover aspects and dynamics of the human / machine relationship, which could project us into ways of living that are also very different from those we are used to until now, with a vigilant objective discernment of the good and evil in human action. Philosophy integrates theology by seeking, within the horizon of reason complementary to faith, to delimit the boundaries of the person and of human nature with respect to the machine. The answer of the philosophy of the person justifies a human-centric vs. a techno-centric horizon, recognizing at the center the dignity of the human person that cannot be reduced to a machine or functions.